2021
DOI: 10.1002/2211-5463.13161
|View full text |Cite
|
Sign up to set email alerts
|

CDX2 regulates interleukin‐33 gene expression in intestinal epithelial cells (LS174T)

Abstract: Dysregulation of interleukin‐33 (IL‐33) has been implicated in the pathogenesis of several autoimmune and inflammatory diseases, but few studies have examined transcriptional regulation of the IL33 gene. In the intestines, gene regulation is controlled by a transcription factor network of which the intestinal‐specific transcription factor CDX2 is a key component. In this study, we investigated whether CDX2 regulates IL33 mRNA expression. We examined IL33 mRNA expression in primary colonic epithelial cells from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…62 Whether P2X7 can regulate any transcription factor that induces IL-33 expression, such as CDX2, remains unclear. 69 The exact mechanism by which P2X7 regulates IL-33 production remains unclear and represents a topic for future studies. In addition, rIL-33 pretreatment significantly protected Panx1 −/-→ WT mice against LPS-induced endotoxemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…62 Whether P2X7 can regulate any transcription factor that induces IL-33 expression, such as CDX2, remains unclear. 69 The exact mechanism by which P2X7 regulates IL-33 production remains unclear and represents a topic for future studies. In addition, rIL-33 pretreatment significantly protected Panx1 −/-→ WT mice against LPS-induced endotoxemia.…”
Section: Discussionmentioning
confidence: 99%
“…Another study also reported that the P2X7 receptor was involved in IL‐33 production by increasing the concentration of Ca 2+ 62 . Whether P2X7 can regulate any transcription factor that induces IL‐33 expression, such as CDX2, remains unclear 69 . The exact mechanism by which P2X7 regulates IL‐33 production remains unclear and represents a topic for future studies.…”
Section: Discussionmentioning
confidence: 99%
“…NFE2L3 can bind the regulatory sequences of the Il-33 locus and promote its expression ( 17 ) in colorectal cancer cells. CDX2 directly binds and promote the intronic enhancer activity in the IL33 gene in primary colonic epithelial cells from healthy humans and epithelial cell lines ( 18 ). Friend leukemia virus integration 1 (Fli1), whose deficiency is a predisposing factor of systemic sclerosis (SSc), occupies the IL33 promoter in dermal fibroblasts and represses IL33 expression.…”
Section: Discussionmentioning
confidence: 99%